2015
DOI: 10.1021/je501044u
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Biphasic Systems Composed of Ionic Liquids and Acetate-Based Salts: Phase Diagrams, Densities, and Viscosities

Abstract: Ionic-liquid-based aqueous biphasic systems (IL-based ABS) have been largely investigated as promising extraction and purification routes. In this context, the determination of their phase diagrams and the physical properties of the coexisting phases are of high relevance when envisaging their large-scale applications. Low viscosities improve the mass transfer and reduce energy consumptions, while the knowledge on their densities is important for the equipment design. In this work, novel phase diagrams for aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…As well‐established in the literature, the toxicity of ionic liquids highly depends on their chemical structure . Hence, tetraakylammonium and phosphonium‐based ILs have been mainly investigated due to their lower toxicity, low‐cost, and high ability to form ABS . In fact, we have previously shown that the ILs affinity for water addressed by their hydrogen‐bond basicity and acidity correlates well with the ABS formation ability .…”
Section: Resultsmentioning
confidence: 99%
“…As well‐established in the literature, the toxicity of ionic liquids highly depends on their chemical structure . Hence, tetraakylammonium and phosphonium‐based ILs have been mainly investigated due to their lower toxicity, low‐cost, and high ability to form ABS . In fact, we have previously shown that the ILs affinity for water addressed by their hydrogen‐bond basicity and acidity correlates well with the ABS formation ability .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the extraction efficiencies of AGB‐ILs ABS for amino acids range between 65% and 100%, which are superior to those obtained by conventional polymer‐based ABS . It is also important to highlight that IL‐based ABS display a lower viscosity than conventional systems formed by polymers, and usually display faster phase separation rates. Extraction efficiencies for L‐tryptophan ranging between 72% and 99% with ABS composed of imidazolium‐based ILs and potassium citrate (K 3 C 6 H 5 O 7 ) have been reported, yet using imidazolium‐based ILs, a strong salting‐out species, and higher amounts of salt (20 wt%) .…”
Section: Resultsmentioning
confidence: 99%
“…32 Cholinium-based IL features combined with the potential benefits of ABS lead to high-performance separations besides other advantages such as quick phase separation and low viscosity favoring mass transfer. 33,34 As mentioned, ABS composition is markedly versatile. This technology will allow the design of an integrated process, bridging the solvents used in the extraction and purification steps of an industrially favorable process.…”
Section: Introductionmentioning
confidence: 98%
“…Owing to their aqueous environment, they are recognized as an appropriate technology for the recovery and purification of biomolecules and other biologically active substances . Cholinium‐based IL features combined with the potential benefits of ABS lead to high‐performance separations besides other advantages such as quick phase separation and low viscosity favoring mass transfer . As mentioned, ABS composition is markedly versatile.…”
Section: Introductionmentioning
confidence: 99%